Niezborność indukowana chirurgicznie po bimanualnej fakoemulsyfikacji przez mikrocięcie oraz po standardowej fakoemulsyfikacji zaćmy - Wilczyńska, Olena; Wilczyński, Michał; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: The purpose of this study was to compare surgically induced astigmatism (SIA), after bimanual phacoemulsification performed through a 1.7 mm superotemporal clear corneal microincision (B-MICS), and after coaxial phacoemulsification performed through a 3.2 mm superotemporal clear corneal incision, calculated with various mathematical methods. Material and methods: Group 1 consisted of 29 eyes after bimanual phacoemulsification performed through a 1.7 mm superotemporal clear corneal microincision. Group 2 consisted of 31 eyes after coaxial phacoemulsification performed through a 3.2 mm superotemporal clear corneal incision. Ophthalmic examination was performed preoperatively, 1 day, 7 days, 1, 3 and 6 months postoperatively. We performed autorefractometry, keratometry, tonometry and visual acuity testing (UCVA and BCVA). SIA was calculated using: vector method, vector decomposition, Cravy’s and Naeser’s method. Results: There was no difference in mean UCVA and BCVA between the groups in the whole observation period. In vector method SIA did not differ significantly between the groups during the whole follow-up. In vector decomposition (C90 component), SIA was higher in group 2 than in group 1, one day and 1 month postoperatively. Cravy’s and Naeser’s method showed that SIA in group 2 was significantly higher as long as the 1-st month postoperatively. In the final examination, there was no significant difference in SIA values between the groups for all methods of calculations. Conclusions: Technique B-MICS through a 1.7 mm incision offers equally good functional results, as standard phacoemulsification through 3.2 mm superotemporal clear corneal incision. The SIA axis was more stable in microincision group in the whole follow-up period.